Education on clean living behavior and rational use of vitamins through comic media as an effort to empower RA IT Cendekia students, Demak Regency - Indriyati Hadi Sulistyaningrum; Donna Muin; Prasojo Pribadi; Elmiawati Latifah; Arifin Santoso (Universitas Muhammadiyah Magelang, 2023)
This community service's goal is to prepare children for the New Normal by educating them about the corona virus, media and transmission methods, signs of infection, physical and social isolation, and how to adjust to and discipline strict measures to prevent transmission. The method of this dedication is by socializing and practicing how to wash hands according to WHO, cleaning objects that can be intermediaries for transmission, wearing masks, keeping a safe distance, increasing self-immunity by exercising diligently, taking vitamins and consuming nutritious food. Every person, including children, should take the necessary precautions to prevent the spread of the Corona virus. The presence of discipline in this prevention effort and the ability to adjust to the new normal will be a turning point in the battle against the corona virus.